Local Wisdom-Based Articulate Storyline Application: A New Way to Improve Reading Literacy for Elementary School Students in the West Papua Region - Nurul Istiq'faroh; Supriyati Fatma Rabia; Zaenal Abidin; Hendratno Hendratno; Amiruddin Hadi Wibowo; Ma Thanh Thanh Hoang (Journal of Innovation in Educational and Cultural Research, 2024)
Literacy is crucial for instructors and students because it promotes understanding in reading, writing, and communication tasks. To provide various benefits, this study incorporates local knowledge into Articulate Storyline educational media. In response to the difficulties mentioned, this study attempts to use the Articulate Storyline program as a teaching tool to increase students' reading literacy. This study employs a quantitative methodology and focuses on factors and how they interact. The one-shot case study approach was employed to investigate the learning program's immediate effects. This design focuses on observing the impact at a single time point without using a control group. The study was conducted in SD INPRES 9 and SD INPRES 50 Papua, focusing on 4th-graders. As a result of receiving the same treatment, the high, medium, and poor groups have various degrees of literacy. Compared to other groups, the high group has superior literacy, whereas the medium group has better literacy than the low group. By encouraging active and significant engagement, technology in education raises the standard of learning. All student groups benefit significantly from developing literacy skills in primary schools since it allows them to decide for themselves what information to trust.